Financial Neglect and Children's Right to Education: Issues on the Maintennace of Children After Divorce in Muslim Marriages in Malaysia - Maheran, Makhtar; Khairun-Nisaa, Asari; Farhanin, Abdullah Asuhaimi (2016)
Divorce among Muslims married couples in Malaysia occurs once in every 15 minutes. The rate of divorce in among Muslims couples is as twice as higher as compared to non-Muslims couples and has become an alarming issue. Children are the most affected individuals from this separation not only in terms of social and emotional aspects but also in financial aspect. Thus, this paper adopted a qualitative approach by way of analyzing the laws, international conventions and related cases in discussing the concept of right to education. Furthermore, it attempts to discuss the financial implications of divorce to the children‘s right to education particularly when the father fails or unable to pay the maintenance to the children. Though the right to education is guaranteed in Malaysia and that the government had abolished school fees, the cost of education is still high and it causes a heavy burden to the single mother to send every child to school. Therefore, enforcement of judgment order by the court needs to improve in order to protect the best interest of children i.e. for their right in respect of education